Biomechanical analysis of the lower extremity during a back salto - Cornelius, W. L. (Technique, 1996)
There are a number of biomechanical considerations in the lower extremity during gymnastics performance. The gymnastics coach can provide a significant contribution to effective performance by being aware of how these considerations can enhance skills and combinations. This could apply to improving gymnastics technique or in reducing a predisposition to injury. The biomechanical structural units such as, the iliosacral, hip, knee, ankle, subtalar, and metatarsophalangeal joints play a primary role in how effectively the gymnast performs These structural units must possess both stability and mobility if the gymnast is to move explosively, artistically, and with control. The purpose of this discussion is to examine the anatomical and mechanical aspects of the lower extremity during the performance of a handstand snap-down to a back salto, pike position.